How employee corporate social responsibility participation promotes pro-environmental behavior - Min, Yan Ai; Hao, Ma; Yang, Xiao; Ling, Deng Yu; Yuan, Jiang Si (Frontiers in Earth Science, 2024)
Introduction: Urban resilience is suffering from the challenges of climate change. The increasing volatility of climate change and its impact on urban resilience necessitates a deeper understanding of how internal organizational behaviors can contribute toward sustainable city development. Pro-environmental behavior is one of the important methods of affecting climate change and enhancing urban resilience. This study investigates how employee participation in corporate social responsibility activities promotes pro-environmental behavior and its mechanism. Methods: This research was conducted an online survey of 262 employees from 22 industries in mainland China. To mitigate the bias arising from self-reported assessments by the employees, the data were collected at two time points. Results: Empirical research reveals that employee participation in corporate social responsibility is positively related to employee pro-environmental behavior; these empirical findings not only support how psychological ownership mediates the link between corporate social responsibility participation and pro-environmental behavior but also indicate how employee engagement acts as an intermediary mechanism in enhancing this positive association. Moreover, the chain mediation effect of psychological ownership and employee engagement in the positive link between corporate social responsibility participation and pro-environmental behavior is found to be significant. Discussion: These findings not only enrich the effects of the mechanism of corporate social responsibility participation on employee behavior by introducing new theoretical perspectives but also deepen understanding of the antecedents promoting employee pro-environmental behavior, thereby contributing to the improvement of urban resilience in the face of climate change.